Echocardiographic estimate of pulmonary artery pressure in sarcoidosis patients, a multi-national study - Huitema, Marloes; Post, Marco; Grutters, Jan; Wells, Athol; Kouranos, Vasilis; Shlobin, Oksana; Nathan, Steven; Culver, Daniel; Barney, Joseph; Gupta, Rohit; Carmona, Eva; Alhamad, Esam; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Introduction: Echocardiographic measurement of  the right ventricular systolic pressure (RVSP) is commonly used for estimating systolic pulmonary artery pressure (PASP) measured during right heart catheterization (RHC) in patients suspected for pulmonary hypertension (PH). Generally, there is a strong correlation. However, this has been reported as less robust in sarcoidosis. We analyzed factors influencing the relationship between RVSP and PASP in sarcoidosis.Methods & Results: Data of patients with and without sarcoidosis associated PH who had both a measurable echocardiographic RVSP and invasive PASP were collected from the RESAPH registry, PULSAR study and Cincinnati Sarcoidosis Clinic database (n=173, 60.1% female, mean age 56.0±9.5years). Among them, 124 had PH confirmed by RHC. There was a strong correlation between PASP and RVSP (r=0.640). This correlation was significant in both male and female, white or non-white, (forced vital capacity) FVC >60%, and presence of fibrosis (p50mmHg was associated with worse survival.Conclusions: In this multicenter cohort of sarcoidosis patients, we found a significant correlation between RVSP as determined by echocardiography and PASP measured by RHC. Over- or underestimation of PASP occurred frequently. Therefore, echocardiography alone to screen for pulmonary hypertension in sarcoidosis should be used with caution.